Effect of liquid swine effluent on the initial growth of forage corn under greenhouse conditions - Peña Caurino, M. Y. (2025)
The use of organic effluents from livestock farming as biofertilizers for agriculture represents a viable solution for the management of swine waste. The research aimed to evaluate the effect of swine liquid effluent on the growth of hybrid corn for forage purposes. A pot experiment was designed to determine the effect of liquid effluent applications of treatments 21 days after planting. The biofertilizer treatments applied to the irrigation water in the pots were 0.00 (control), 9.45, 18.90, 28.35, 37.80 and 47.25 m3 ha-1. Applications of 37.80 and 47.25 m3 ha-1 improved stem diameter, foliage, and total fresh weight. For root fresh weight and root volume, the highest values occurred with applications of 18.90 to 47.25 m3 ha-1. The nutrient content (N, P, K) of corn treated with swine liquid effluent showed an incremental trend in foliage and roots, as well as the absorption of macronutrients due to the effect of the treatments. Liquid swine effluent showed a promising role as an organic fertilizer for the cultivation of maize for forage purposes, promoting higher biomass production and macronutrient uptake.